2007
DOI: 10.1016/j.seizure.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of some risk factors in children with epilepsy compared to their controls

Abstract: The most important risk factors for epilepsy in this study were neurological impairment, history of atypical febrile seizures, severe head injury and a low apgar score. Other important risk factors were moderate head trauma and a history of epilepsy in the family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
3
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 45 publications
2
29
3
12
Order By: Relevance
“…History of febrile seizures increased five-fold the risk of developing epilepsy, which is consistent with results of previous studies (Daoud et al, 2003;Cansu et al, 2007). The strong association with febrile seizures does not reflect a causal relationship, but may mean that febrile seizures represent an early expression of a low seizure threshold in patients genetically predisposed to epilepsy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…History of febrile seizures increased five-fold the risk of developing epilepsy, which is consistent with results of previous studies (Daoud et al, 2003;Cansu et al, 2007). The strong association with febrile seizures does not reflect a causal relationship, but may mean that febrile seizures represent an early expression of a low seizure threshold in patients genetically predisposed to epilepsy.…”
Section: Discussionsupporting
confidence: 90%
“…In the Arab world where first-degree consanguineous marriages represent more than 60% of all unions (Etude, 2007), the association to epilepsy has been suggested by some studies (Asadi-Pooya, 2005;Choueiri et al, 2001;Khedr et al, 2013;Benamer and Grosset, 2009;Bourrous et al, 2010) and refuted by others (Daoud et al, 2003;Cansu et al, 2007;Huseyinoglu et al, 2012;Yemadje et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…History of epilepsy in the family in patients with CP will increase the risk of developing epilepsy. 24 In this study, history of epilepsy in the family was not proven to be a risk factor for epilepsy in spastic CP children. Kulak et al and bruck et al 15 showed different result that may due to information bias about the history of epilepsy in the family in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Results of several other studies of the familial occurrence of epilepsy have reported various results mainly related to the method of case ascertainment. A case-control study from our country revealed an increase in the history of epilepsy in first-, second- and third-degree relatives (6.42-, 3.09-, and 2.66-fold) [16]. In a population-based study in Pakistan, Aziz et al [9] reported that 32% of the epileptic patients had relatives with epilepsy.…”
Section: Discussionmentioning
confidence: 99%